(untitled) (Jurnal Spektran, 2026)
Unsignalized intersections are critical components of urban road networks whose performance is highly influenced by side frictions, including pedestrians, parked vehicles, maneuvering vehicles (entering/exiting), and slow-moving vehicles. High side friction can reduce intersection capacity and increase vehicle delays, leading to congestion. This study aims to analyze side friction conditions, evaluate intersection performance based on the Indonesian Highway Capacity Guideline (PKJI), and assess the impact and sensitivity of side friction on delays at the Jl. Tukad Pakerisan – Jl. Tukad Sanghyang intersection. Field surveys were conducted on weekdays and weekends during morning (07:00–09:00), afternoon (12:00–14:00), and evening (16:00–18:00) peak hours. Data collected included traffic volume, geometric conditions, side friction frequency, and field delays. Analysis was performed using PKJI 2023, polynomial regression, and sensitivity analysis. The results showed that the intersection side friction was categorized as very high, with the highest frequency reaching 2725, dominated by entering and exiting vehicles, with a frequency of 2569. Based on PKJI 2023 analysis, the highest traffic flow reached 2159 pcu/hour, with an intersection capacity of 2267.280 pcu/hour, a degree of saturation of 0.952, and average delay of 17.164 sec/pcu, corresponding to level of service C. Polynomial regression analysis indicated that entering and exiting vehicles had the greatest influence on delay, with an R² value of 0.9926. Sensitivity analysis revealed that the 07.00–08.00 period had the highest sensitivity value of 0.00414, indicating that slight increases in entering and exiting vehicle activity could significantly increase intersection delay.